The Effect of Financial Literacy, Financial Experience, and Income Level on Family Financial Behavior - Syahida Afifi; Hariyati Setyorini (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Penelitian ini berjudul